Originally Posted by

**Fallen186** Find the second derivative

$\displaystyle

f(x) = ((x-2)^3)/(x^2)

$

Attempt:

f'(x)/g(x) = (f'*g-g'*f)/(g^2)

$\displaystyle

f'(x) = ((3*(x-2)^2)*(x^2)-(2x)*((x-2)^3))/(x^4)

$

I do it again

f(x)/g(x) = (f'*g-g'*f)/(g^2)

f(x)*d(x) = f'd + d'f

f''(x) = ((6(x-2)*x^2+2x*(3*(x-2)^2) -(2*((x-2)^3)+2x*(3(x-2)^2))*(x^4)-(4x^3)*((3*(x-2)^2)*(x^2)-(2x)*((x-2)^3))/(x^8)

*Sorry the math thing can't fit the size of this

Simplifying doesnt give me the right answer. The correct answer is $\displaystyle 24(x-2)/(x^4)$.

How do i do this?